Outcomes of young patients diagnosed with locally advanced rectal cancer - Habib, Rosemary (J Gastrointest Oncol, 2021)
BACKGROUND: The incidence of rectal cancer is higher in the older population. In developed nations, there has been a rise in incidence in young onset colorectal cancer (CRC). We examined the outcomes of locally advanced rectal cancer (LARC) in younger patients (yRC) compared with older patients, using a retrospective audit. METHODS: All cases of LARC referred to two tertiary referral cancer centres in Western Sydney were examined. Patient demographics, presenting symptoms, treatment, relapse free survival (RFS), overall survival (OS) and progression free survival (PFS) were obtained. Under 50 years old was used as the cut-off age for defining yRC. RESULTS: All 145 consecutive patients were treated for LARC, including 28 in the yRC and 117 in the older patient group. Median follow-up was 54 months. yRC were more likely to complete neoadjuvant therapy (100% vs. 86%; P=0.032) and to undergo more extensive surgical procedures (24% vs. 2%, P<0.0001). yRC were more likely to have microsatellite high (MSI) tumours (30% vs. 4.7%; P=0.003). yRC demonstrated significantly poorer RFS compared with the standard group (HR 2.79; median RFS 4.67 vs. 16.02 months; P=0.023). In the relapsed setting, yRC had poorer PFS compared with the standard group (median PFS 2.66 vs. 9.70, P=0.006, HR 3.04). A difference in OS was also seen between the two groups, with yRC demonstrating poorer OS (median OS 40.46 vs. 58.26 months, HR 3.48, P=0.036). CONCLUSIONS: Patients under 50 years with LARC are more likely to have MSI tumours with a more aggressive disease course and poorer RFS, PFS and OS. Initiatives to improve early detection of these patients may improve outcomes. Further research is necessary to understand this disease and optimise its treatment.